Man and banner - Sahl, Ted (photographer):::Creator::::::::::::
The upper half of the photograph shows a bearded man at the National March on Washington for Lesbian and Gay Rights. The lower half shows a banner that reads, "San Francisco". Above the wording is a graphic of a bird with its wings spreadout and a crown.